The Interplay of Individualistic Factors on Divergent Thinking: An Explored Mediating Effect of Problem-Solving Ability Among Engineering Students - V, Sandhiya; Bhuvaneswari, Mohanraj (Journal of Engineering Education Transformations, 2025)
Divergent thinking (DT) is a cognitive ability that enables individuals, especially engineering students, to tackle complex problems with originality and creativity. This study examines the mediating effect of problem-solving ability (PSA), on DT, intelligence, memory, and academic performance among engineering students. The study was carried out on 123 final-year engineering students aged 20–21 (mean age = 20.41; SD age =.493) from Vellore district, Tamil Nadu. A descriptive crosssectional study was conducted, and standardized psychometric questionnaires were used to collect the primary data. The Statistical Package for the Social Sciences (SPSS-26) and Andrew Hayes Macro Process 4.3 software were used to analysis statistical tests like the independent sample t-test, Pearson correlation, and mediation analysis. The results provided empirical evidence on the mediating effect of problem-solving ability on the association between intelligence, memory, and DT among engineering students. The study also provided suggestions for future research on the subject.